Juridical Review of the Role of Notary in the Preparation of Land Sale and Purchase Deed in Indonesia - Baan, Bram B; Khair, Otti Ilham; Sulis Setyowati; Judijanto, Loso; Lumban Gaol, Selamat (Faculty of Law, Universitas Pekalongan, 2024)
The transfer of land rights to purchase and sell land must be conducted under the supervision of an authorized official, commonly known as a Land Deed Official (PPAT) in this context. The authority to execute a legally binding land deed is vested in a Notary. Nevertheless, in this instance, notaries are prohibited from drafting deeds pertaining to land unless they have successfully completed the requisite examination to become a Land Deed Official (PPAT). Furthermore, deeds may be made by the subdistrict head, who acts as a temporary PPAT. The methodology employed by the author is normative legal research (doctrinal legal research). Normative legal research is a form of pure normative legal research, in which the problem under study is a legal scientific one, such as those pertaining to justice, order, and the agreement of will, among others. This research does not concern itself with the legal facts that exist in society. The findings of this research indicate that the role of a notary in the process of making a land sale and purchase deed is limited to the pre-sale of land or the making of an agreement between the seller and the buyer. It can be concluded that only a PPAT (land deed official) is authorized to prepare and execute a land sale and purchase deed.